The Implementation Of Inquiry Based Learning In Teaching English At SMA N 1 Boyolali In 2013/2014 Academic Year - Sangadah, Putri Anif; , Aryati Prasetyarini, S.Pd, M.Pd; , Nur Hidayat, M.Pd (2014)
This research aims to describe the implementation of inquiry-based learning in teaching English at SMA N 1 Boyolali in 2013/2014 academic year. It was done to know the implementation of inquiry-based learning and the principles of implementation of inquiry in teaching English at second grade students of SMA N 1 Boyolali. The type of this research is descriptive qualitative research. The writer gets the data from event, informant, and document. The techniques of collecting data are observation, interview, and documentation. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show that: 1) the implementation of inquiry-based learning in teaching English was not fully complete at XI Science3 of SMA N 1 Boyolali. Teaching techniques used in teaching English are discussion and problem-solving. There are three activities in teaching learning process, such as: exploration, elaboration and confirmation based on the standard process of Education Ministry. 2) The implementation of inquiry-based learning at XI Science3 of SMA N 1 Boyolali was in-line with the principle of inquiry-based learning. There are four principles of implementation inquiry-based learning based on Joe Exline, such as: learning activities are focus on using information skill, the students put at the center of an active learning process, the teacher becomes a facilitator of the learning process, and assessment is ongoing.